Some Socio-Religious Flora of Rupandehi District, Western Nepal - Thapa, Chandra Bahadur (International Journal of Applied Sciences and Biotechnology, 2015)
The present study was carried out to document the indigenous knowledge of local people regarding the use of plant species on socio-religiousactivities during the year of 2012-2013. The indigenous knowledge was documented by using semi-structured interview, focus group discussionand informal discussion with the local people, religious persons and aged people. Altogether 32 plant species belonging to 23 family and 30genera have been documented in Rupandehi district. Among them, 13 species were herbs, 5 species shrubs, 13 species trees and 1 speciesclimber. Use of these plant species in socio-religious activities has helped people to conserve the faith of deities as well as to conservebiodiversity in the area. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12217 Int J Appl Sci Biotechnol, Vol. 3(1): 123-126